Peningkatan Kompetensi Dosen Universitas Islam Batang Hari dalam Membangun Ekosistem Pendidikan Tinggi Ungggul - Adang Ridwan; Ria Karmila; Oryza Syavita (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Higher education institutions play a strategic role in building a quality education ecosystem by strengthening the competency of human resources, particularly educators. As a higher education institution, Batang Hari Islamic University is required to ensure that its lecturers possess the skills to meet the ever-changing developments in science and technology, as well as the needs of society. To address these challenges, community service activities are being implemented to enhance the capacity of lecturers, enabling them to support the creation of a superior and competitive higher education ecosystem. These activities are implemented through various methods, such as workshops, training, and participatory mentoring. The primary focus is on improving digital literacy, mastery of innovative learning methods, scientific publication skills, and quality-based research and community service management. With this approach, lecturers not only gain new knowledge but also practical skills that can be directly applied in daily academic processes. The results of these activities demonstrate a significant increase in lecturers' insights and skills, particularly in the use of digital-based learning technologies, increased productivity of scientific work, and the expansion of academic networks with various partners. These changes contribute to the growth of a more dynamic, collaborative, and innovative academic culture. Overall, these activities have had a positive impact on Batang Hari Islamic University by fostering an academic environment that is responsive to changing times. In this way, universities not only strengthen their competitiveness at the national level, but also have the potential to improve their position on the global stage through competent, creative, and quality-oriented lecturers.